Coping strategies before competition: the role of stress, cognitive appraisal, and emotions - Nogueira, J. M.; Simães, C.; Morais, C.; Mansell, P.; Gomes, A. R. (Sports, 2025)
Sports, and especially competitions, can be a stressful experience for athletes, who often struggle to find and apply strategies to cope with stress. Thus, this study analyzes how different coping strategies anticipated to be employed in an important competition are explained by psychological (i.e., cognitive appraisal and emotions) and person and sports-related factors (i.e., gender, type of sport). Specifically, athletes were asked to complete a protocol 24-48 h prior to an important competition to assess their adaptation to stress related to high performance. The study included 383 athletes (60% male, Mage = 22.9 ± 5.3 years), from individual (swimming and running, n = 157; 41%) and team sports (handball, volleyball, n = 226; 59%) competing in major national leagues. Hierarchical linear regression analyses (enter method) were performed to examine the extent to which coping strategies and coping efficacy were explained by psychological, personal and sport-related variables. Results indicated (a) higher control perception and excitement were related with higher intention to use active coping; (b) being a female athlete, practicing individual sports, and excitement (higher intensity and facilitative value) were associated with a higher intention to use emotional support; (c) being a female athlete, lower coping perception, higher anger intensity, and higher facilitative value of happiness were associated with a higher anticipated use of humor; and (d) being a male athlete, higher anxiety, anger, and happiness intensity, and lower facilitative value of dejection and excitement were associated with higher anticipated use of denial. In sum, the explanation of each coping strategy is distinct and should be analyzed separately.